1997
DOI: 10.1038/nm0397-282
|View full text |Cite
|
Sign up to set email alerts
|

Infection of human cells by an endogenous retrovirus of pigs

Abstract: The possible use of pig organs and tissues as xenografts in humans is actively being considered in biomedical research. We therefore examined whether pig endogenous retrovirus (PERV) genomes can be infectiously transmitted to human cells in culture. Two pig kidney cell lines spontaneously produce C-type retrovirus particles. Cell-free retrovirus produced by the PK-15 kidney cell line (PERV-PK) infected pig, mink and human kidney 293 cell lines and co-cultivation of X-irradiated PK-15 cells with human cells res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
829
0
19

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,075 publications
(867 citation statements)
references
References 42 publications
19
829
0
19
Order By: Relevance
“…The risk of conventional zoonosis led us to isolate islets from specific pathogen-free (SPF) pigs [1,2,3,4,5,6,7,8]. However, there is also a risk of transmitting porcine endogenous retroviruses (PERV) [9,10,11,12]. The ability of PERV [10] produced by pig cells to infect human cells in vitro has been documented [8,9,13,14,15,16,17].…”
Section: Pcr-derived Monitoring Of Perv Infection and Microchimerism mentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of conventional zoonosis led us to isolate islets from specific pathogen-free (SPF) pigs [1,2,3,4,5,6,7,8]. However, there is also a risk of transmitting porcine endogenous retroviruses (PERV) [9,10,11,12]. The ability of PERV [10] produced by pig cells to infect human cells in vitro has been documented [8,9,13,14,15,16,17].…”
Section: Pcr-derived Monitoring Of Perv Infection and Microchimerism mentioning
confidence: 99%
“…However, there is also a risk of transmitting porcine endogenous retroviruses (PERV) [9,10,11,12]. The ability of PERV [10] produced by pig cells to infect human cells in vitro has been documented [8,9,13,14,15,16,17]. PERV mRNA and full-length endogenous retroviral genome were expressed in all pigs tested [9,15,18,19], including SPF pigs [5,20].…”
Section: Pcr-derived Monitoring Of Perv Infection and Microchimerism mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial reports suggested the host range of PERV to be restricted to porcine origin, but in 1997 Type C retrovirus from PK-15, termed PERV-PK was reported to infect human, mink and porcine cell lines. Because of the shortage of procuring human tissues, PERV found in the 1970s was checked for its safety in xenotransplantation and new treatments was evolved based on porcine tissues or cells, as in vitro infection of human cells lines, such as HEK-293, was demonstrated in 1997 [5]. The described PCR-based assays can be used to screen porcine tissue for PERV sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Host range analysis by the vector transduction assay has showed that PERV-A and PERV-B viruses have wider host ranges, including several human cell lines than PERV-C viruses, which infect only two pig cell lines and one human cell line. Two of the three identifi ed receptor classes of PERV, distinguished by their envelope sequence and tropism, have been shown to be capable of replicating in human cells in vitro [3][4][5][6]. Clinical trials to date with live pig xenograft tissues include perfusion with pig livers or porcine hepatocytes as a bridging strategy for hepatic failure, use of pancreatic islet cells as a treatment for chronic diabetics and implantation of fetal neuronal tissue as a therapy for Parkinson's disease [7].…”
Section: Introductionmentioning
confidence: 99%